Erectile Dysfunction Among Patients with Hypertension and AssociatedSocio-Demographic Factors - Satti, Raja Rizwan Ul Haq; Rasheed, Syed Abdul; Gul, Rubab; Athar, Muhammad Hammad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of erectile dysfunction among the patients of hypertension and analyze the associated socio demographic factors.Study Design: Cross sectional analytical study.Place and Duration of Study: Medicine Department, Pak Emirates Military Hospital Rawalpindi, from Aug to Oct 2018.Methodology: Two hundred and five married male patients of hypertension diagnosed for more than one year by a consultant medical specialist were included in the study by non-probability consecutive sampling. Erectile dysfunction (ED) was assessed by using the International Index of Erectile Function-5 (IIEF-5). Socio-demographic factors in the study included age, education, smoking, poly-pharmacy and duration of illness.Results: Out of 205 patients of hypertension, 95 (46.3%) patients had no ED, 57 (27.8%) patients had mild, 17 (8.3%) patients had moderate and 12 (5.2%) patients had severe ED. Mean age of the study participants was 39.94 ± 4.14 years. Mean duration of hypertension among the patients in this study was 6.24 ± 2.78 years. Increasing age, tobacco smoking, poly-pharmacy and long duration of illness had statistically significant association with ED (p-value